KUKIS SAGU TINGGI KALSIUM FORTIFIKASI TULANG IKAN TUNA DAN RUMPUT LAUT Caulerpa sp. - Novalina Maya Sari Ansar; Jimi Palawe; Trivonia Kerol Talete; Novelia Tatinting; Wendy Alexander Tanod; Jefri Antonius Mandeno; Frets Jonas Rieuwpassa; Eko Cahyono (EnviroScienteae, 2021)
Calcium is one of the important minerals in the physiological regulation of the immune system. Until now, tuna bone waste has not been widely used to fulfill human health needs. This study aims to obtained a high calcium sago cookies formulation by utilizing local resources, like seaweed (Caulerpa sp.) and tuna bone. Research methods include 1). Production of tuna bone porridge; 2). Production of lahe (Caulerpa sp.) porridge; 3). Production of sago flour; 4). Production of sago cookies; and 5). We were testing the chemical and physical quality of sago cookies. The univariate analysis showed that formula 1 sago cookies was preferred by the panelists and was close to the control formula. The chemicals analysis of the formula 1 sago cookies showed carbohydrates (57.95 ± 0.06%); water (5.09 ± 0.04%); fat (25.93 ± 0.08%); ash (5.90 ± 0.04%); protein (5.14 ± 0.10%); total energy (485.67 ± 0.05 kcal/100 g); energy from fat (233.33 ± 0.70 kcal/100 g); insoluble dietary fiber (20.29 ± 0.01 %); calcium (998.64 ± 8.60 mg/100 g); and phosphorus (5765.35 ± 40.36 mg/kg). The present findings confirm that panelists prefer the formula 1 sago cookies with a chemical composition according to quality requirements Indonesia National Standard (SNI 2973:2011) and nutritional adequacy recommended for Indonesian people (AKG 2019). In addition, the chemical composition contained in prototype sago cookies of formula 1 has the potential to become a high-calcium snack.